Artificial Intelligence Integration in Strategic HRM: A Bibliometric Approach to Enhancing Organizational Performance - Harry Yulianto; Iryani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the integration of Artificial Intelligence (AI) into Strategic Human Resource Management (SHRM) and its contribution to enhancing organizational performance using a bibliometric approach. The research method involves analyzing data from Scopus and Crossref databases with the help of VOSviewer software to map research trends, keyword relationships, and publication distributions. The findings reveal that AI plays a significant role in optimizing HR processes, such as data-driven decision-making, productivity enhancement, and more efficient talent management. Key trends include innovations in HR practices, the utilization of big data, and sustainability practices (green HRM). The analysis identifies a significant increase in publications since 2020, reflecting growing academic interest in this topic. This research provides practical significance by helping organizations understand the strategic benefits of AI in addressing HR challenges and driving sustainable performance. The findings of this study are expected to serve as a reference for future research exploring AI implementation across various organizational contexts.